The Effect of Shading and Nutrient Addition on the Microphytobenthos, Macrofauna, and Biogeochemical Properties of Intertidal Flat Sediments - Tolhurst, Trevor J.; Chapman, M. G.; Murphy, R. J. (Frontiers in Marine Science, 2020)
Proliferation of urban structures and mangrove forests in estuaries are altering the shading of intertidal sediments. Urbanization also tends to increase nutrient loads in estuaries, which can have numerous direct and indirect effects on estuarine flora and fauna. Mangrove canopy shades the sediment and provides nutrients to the ecosystem via leaf litter. Microphytobenthos, macrofauna, sediment erodibility, and various biogeochemical properties of sediments have been shown to differ significantly between unshaded intertidal sediment and nearby sediment under a mangrove canopy. This study tested the effects of experimental manipulation of shading and addition of nutrients on the microphytobenthos, macrofauna, sediment erodibility, and selected biogeochemical properties of exposed intertidal flat next to the seaward edge of a mangrove forest. In the first of two experiments, plots were shaded with roofs to give lightly shaded plots and heavily shaded plots, for comparison with unshaded control plots; nutrients were added in an orthogonal design. Sediment and benthos were sampled after 2 weeks. Nutrients were omitted in the second experiment, with plots sampled after 2 weeks or approximately 3 months. The only effect of nutrients was a small negative effect on chlorophyll a and colloidal carbohydrate. Light shading (clear roofs) generally increased measures of microphytobenthos biomass (e.g., Fo and chlorophyll a) and biogeochemical properties associated with microphytobenthos such as colloidal carbohydrate. Heavy shading (black roofs) generally decreased measures of microphytobenthos biomass and microphytobenthos-associated biogeochemical properties. Effects on the fauna were much smaller and inconsistent with previous studies, after 3 months, assemblages were different under heavy shading compared to light shading and unshaded control plots, with differences primarily driven by changes in the oligochaetes. Natural or anthropogenic changes in shading at larger spatial scales are likely therefore to directly and indirectly change microphytobenthos, sediment properties, macrofauna and hence ecosystem functions; but any flow-on effects to the fauna are difficult to predict without further experiments to understand the indirect and direct responses of fauna to changing microphytobenthos and properties of intertidal sediment.